Microstructure design strategies to enhance aroma and tastant availability in foods - Su, Katy (2021)
Nutritionally improving foods through reduction of sugar, salt and fat in foods is important to decrease the prevalence of diet related diseases. Common strategies used in the food industry often result in changes in perception of texture and flavour. The role of sugar in confectionery gels extends beyond just taste and sweetness purposes, as it also affects a variety of properties such as structure, texture and shelf life. Therefore, nutritionally improving confectionery gels using conventional strategies is difficult and it is important to develop novel routes to reformulate and modify energy density without compromising sensory quality.